Efecto de la sustitucion del maiz por citropulpa y cascarilla de arroz en la alimentacion de pollos de engorde (ING) - Rodríguez Zelaya, José (1994)
360 one-day-old, straight-run Indian River chicks were distributed in a complete randomized design to determine the effect of the substitution of corn for citropulpa (CP) or rice husk (RH) in their diet, during the starting (28 days) and finishing (21 days) periods. Water and feed were offered ad libitum.The diets used were: a) commercial feed (control), b) 5% citrus pulp (70% coffee pulp + 30% citrus pulp) and c) 5% rice husk in the diet and weght gain (g/bird/day), feed intake (g/bird/day), feed conversion and carcass yield (%) were evaluated in both periods. In addition, an economical analysis was carried out.The results show that the group of birds fed with RH presented the largest weight gain and feed intake. The best feed conversion was in the control group and there were significative statistical differences (P≤0, 05) between treatments during the starting period for this variable. The birds fed with the RH showed the largest carcass yield followed by the control and the CP groups.Related to the economical analysis, the group fed with RH presented the best results in terms of profit/bird and the CP group the worst.